(untitled) (Research, Society and Development, 2022)
Platonia insignis Mart. is a vegetable of the Clusiaceae Lindl., family that is popularly known as “bacuri” in Brazil. It is widely used in folk medicine to treat human diarrheas and inflammatory diseases. It has antiparasitic activity, antioxidant, anticarcinogenic action, in addition to vasorelaxant potential. The present study investigates the leishmanicidal, cytotoxic and genotoxic activities in different biological systems, as well as the chemical constituents of hexane extract from P. insignis seeds. The analysis of the non-volatile constituents was analyzed by GC/MS. A total of sixteen main constituents were detected in the saponifiable material (fatty acid methyl esters, ethyl ester, alcohols and hydrocarbons). In unsaponifiable fraction, nineteen constituents were detected, including a series of n-alkanes and prenylated xanthones gamma-mangostin as main component (70.23% of the total components). The results indicated that the seed hexane extract significantly inhibits the growth of promastigote forms of Leishmania amazonensis (IC50), displayed a significant toxicity against Artemia salina Leach and cytotoxicity and genotoxicity in V79 cell lines.